Five Misconceptions About Interview Modes or: How to Improve Our Thinking About Face-to-Face Versus Remote Interviewing - Johannessen, Lars E. F.; Rasmussen, Erik Børve; Haldar, Marit (International journal of qualitative methods, 2025)
New technology brings new methodological opportunities. While long limited to face-to-face interviewing, today’s interview researchers can choose from a plethora of options, including email, instant messaging, telephone, and video interviews. Consequently, the issue of interview modes and their relative strengths and weaknesses has received increased attention. In this article, we take stock of existing writings on interview modes in qualitative interview research. Drawing on key insights from more general theorizing about face-to-face and remote interaction, we identify and challenge five key assumptions in writings about interview modes: (1) that physical copresence ensures more and better data; (2) that interview modes have determinate effects on interaction; (3) that remote interviewing should seek to replicate face-to-face interviewing; (4) that interviews modes should be held constant within each study; and (5) that face-to-face interviewing is unmediated. We counter each assumption with a series of more productive methodological principles and advance instead a view we call interview mode pluralism, which offers a more nuanced and relational understanding of the strengths and weaknesses of different interview modes. The article thus helps increase the methodological literacy of those conducting and evaluating qualitative interview research, enhancing the likelihood that researchers select those tools best suited for their tasks, and reducing the chance that evaluators dismiss research based on their methodological prejudice.